Living with systemic lupus erythematosus in 2020: a European patient survey - Cornet, Alain; Andersen, Jeanette; Myllys, Kirsi; Edwards, Angela; Arnaud, Laurent (Lupus science & medicine, 2021)
ObjectiveThe aim of this study was to analyse the 2020 burden of Systemic Lupus Erythematosus (SLE) in Europe, from the patients’ perspective.MethodsIn May 2020, Lupus Europe, the European umbrella patient association for SLE, designed and disseminated a multilingual anonymous online survey to individuals with a self-reported physician’s diagnosis of SLE living in Europe.ResultsData from 4375 SLE survey respondents (95.9% women, median age: 45 (IQR: 36–54) years, 70.7% Caucasians) from 35 European countries were analysed. The median age at SLE diagnosis was 30 years (IQR: 22–40) and the median diagnosis delay was 2 years (IQR: 0–6). The most commonly affected organ-systems included the joints (81.8%) and skin (59.4%), with renal involvement in 30%. Another diagnosis was given before that of SLE in 45.0%, including psychological/mental disorders in 9.1% and fibromyalgia in 5.9%. The median number of symptoms reported was 9 (IQR: 6–11) out of 21, with fatigue most common (85.3%) and most bothersome. The median number of SLE-related medications was 5 (IQR: 3–7), including antimalarials (75%), oral glucocorticoids (52.4%), immunosuppressants (39.8%) and biologics (10.9%). Respondents reported significant impact over their studies, career and emotional/sexual life in 50.7%, 57.9% and 38.2%, respectively. Appropriate access to care was highly variable across countries and care component.ConclusionThis survey underlines the 2020 burden and strong heterogeneity in the care of SLE across Europe, from the patient’s perspective. Altogether, these data may prove crucial to physicians, patients and policy-makers to improve the diagnosis and management of this rare and complex disease.